Estruturas de governança e coordenação no suprimento de cana-de-açúcar para produção de alimentos e bebidas - Trentin, Bruno Ivan Stefanello (2018)
The institutional arrangements instituted by agroindustrial firms in the transactions that occur within productive chains are fundamental in the alignment of incentives for cooperation among agents. In this sense, this research seeks to analyze the structures of coordination and governance existing in the transactions carried out in the production of sugar cane for food and beverage production in Rio Grande do Sul. The theoretical basis for the research is from the authors of Nova Institutional Economics, with particular attention on the Theory of Transaction Costs and Institutional Environment. The two case studies were carried out in two sugarcane agroindustrial firms, duly legalized for sale throughout the country and belonging to two distinct regions of the state of Rio Grande do Sul. In order to collect the primary data, in the period from January to June of 2018 semi-structured interviews were conducted with the representatives of the agroindustrial firms and with three suppliers from each firm under study. The discourse analysis identified that the relationships in the transactions are stable and harmonic, with the firm having an important role in the coordination of the production of sugarcane. The specificities of the raw material and the derivatives are factors of great influence in the constitution of the governance structures, mainly in relation to the production of brown and molasses sugar. The largest investments and the main transaction costs are absorbed by the firms and are related to the characteristics of the institutional environment. The joint analysis of the cases showed that it is possible to verify that factors related to the specificities of the assets and to depend on the region of the state of Rio Grande do Sul where the transactions are carried out, influence the firm's decision to organize the adequate governance structure in the sugarcane- of sugar. The conclusions presented at the end of the study demonstrate that the main sources of transaction costs have their origins in the institutional environment and that the specificities of the assets involved in the process of production and processing of sugarcane are determinant in the adoption of the governance structure used in transactions.